The role of respiratory viruses in the origin and exacerbations of asthma - Papadopoulos, N. G.; Psarras, S.; Manoussakis, E.; Saxoni-Papageorgiou, P. (Curr Opin Allergy Clin Immunol, 2003)
The present review focuses and comments on the increasing body of evidence correlating respiratory viral infections with asthma onset and exacerbations.|Recent data suggest multiple and some time contrasting roles for viral infection in the origin of asthma. These data also indicate that the immune status of the host, including atopy, may interactively contribute to this process, conferring susceptibility or even resistance to the development of asthma in virus-infected individuals. In the presence of asthma, the role of viral infection in triggering exacerbations is clearly established. Chemokine and cytokine responses of the respiratory epithelium, a biased type 1/type 2 cytokine balance, defective costimulation, as well as abnormal neural control have been suggested as possible mechanisms. The importance of concurrent or synergistic effects of allergen exposure is currently under scrutiny.|Viruses may initiate and certainly exacerbate asthma. Mild repeated infections early in life could also stimulate type 1 immune responses conferring protection from atopy and asthma. The host's immune status, the type of viral infection and the timing of exposure to various environmental stimuli are probably the key factors in this process. Mechanistic insights deduced from recent work should allow for the development of intervening strategies in the near future.
Keywords: Asthma Cytokines Humans Respiratory Tract Infections Th1 Cells Th2 Cells Virus Diseases